A Preliminary Study of Exhaled Breath Profiling of GERD-Asthma using an E-nose and Carbon Dioxide Concentration as Biomarkers - Kasnawi Al Hadi; Ni Ketut Anggriani; Arif Budianto; Dewi Alya Nabilla; Dewi Nor Farahin (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
Carbon dioxide plays a vital role in the human body. Many studies confirm that changes in carbon dioxide concentrations can serve as biomarkers for various health problems. This biomarker can be detected using several techniques, including an electronic nose (e-nose). However, there is a limitation in the e-nose's function and development in specific health cases, especially in respiratory or other systems. In line with this, this study aims to develop an economical, simple e-nose based on a CO2 (carbon dioxide) gas sensor and to establish an exhaled breath profile related to asthma and GERD (gastroesophageal reflux disease), which are common daily health problems. For this purpose, 90 exhaled breath samples from three different health conditions were obtained as the primary breath profiling samples: healthy, GERD, and asthma. The samples were measured and analyzed using a simple e-nose based on a high-sensitivity carbon dioxide sensor. The e-nose was calibrated and tested under laboratory-scale procedures, including linearity, accuracy, and sensitivity examinations. Then, the collected samples were classified, analyzed, and interpreted to produce a profile prediction for those health problems. The results show that the e-nose system can measure CO2 gas concentrations in the range of 400-9700 ppm. There are three selective profiles of the exhaled breath samples: healthy (450 to 899 ppm), GERD (3327 to 5381 ppm), and asthma (6612 to 9706 ppm). It can be concluded that the developed e-nose can classify different health conditions. There is a significant difference between healthy, GERD, and asthma samples (p < 0.05). These differences were interpreted as breath profiles with an accuracy level of 84%. This research may contribute to a preliminary investigation of breath profiles for specific health problems, with a rapid response time and high accuracy.